Evaluation, multiplication and deposition of sunflower germplasm accessions in medium term storage: Evaluation, multiplication and deposition of sunflower germplasm accessions in medium term storage - P B SWETHA; M LEELAVATHI; M Y DUDHE (Journal of Oilseeds Research, 2020)
During the year 2018-2019 a total of 700 germplasm lines were multiplied and evaluated during kharif 2018. All the accessions were sown in augmented block design and compared with three checks. Promising accessions were identified with high seed yield and medium oil content. The range for oil content was between 24 and 37%. The germplasm accessions identified for high seed yield and medium oil content were GMU-125, GMU-169, GMU- 251, GMU-272, GMU-396, GMU-928, and GMU-1102. The five accessions identified with 37.0% of oil content included GMU-466, GMU-663, GMU-1091, GMU-1106 and GMU-1140. After complete drying of the seeds, the cleaned seeds from each accession were deposited in the medium term storage (MTS) of IIOR with proper labeling. Out of total harvested seeds approximately 50.0 g of the seeds was packed in airtight aluminium package suitable for medium term storage and remaining seeds were stored as working germplasm.